Mini‐Sized Carbon Nitride Nanosheets with Double Excitation‐ and pH‐Dependent Fluorescence Behaviors for Two‐Photon Cell Imaging. Issue 8 (21st March 2017) - Liu, Jinhua; Zhao, Duoduo; Li, Lin; Weng, Minrui; Zhang, Chengwu; Zhang, Shiyu; Zhu, Jixin; Feng, Yong; Shih, Kaimin; Huang, Wei
Abstract: Synthesis of mini‐sized carbon nitride nanosheets (CNNSs) by traditional methods remains a challenge. Herein, size‐tunable and uniform mini‐sized CNNSs are synthesized by hydrothermal carbonization of a single polyethyleneimine (PEI) precursor. The as‐obtained mini‐sized CNNSs possess uniform size, good hydrophilicity and abundant nitrogen active sites, which not only exhibit double excitation‐ and pH‐dependent fluorescence behaviors, but also two‐photon excitation fluorescence. áThe resulting CNNSs display low toxicity and can be efficiently delivered into live cells for two‐photon fluorescence imaging, offering great potential as fluorescence probes in biochemical applications. Abstract : How to keep clean sheets : Uniform mini‐sized carbon nitride nanosheets (CNNSs) are fabricated by hydrothermal carbonization of single polyethyleneimine precursor. Owing to the unique structure features of tunable size, good hydrophilicity, abundant active sites and low toxicity, CNNSs show double excitation‐ and pH‐dependent fluorescence behaviors, as well as two‐photon fluorescence imaging in live cells.